An alternative approach of competitiveness evaluation for real estate developers - Zhang, Xiaoling; Tan, Yongtao; Shen, Liyin; Wu, Yuzhe (International Journal of Strategic Property Management, 2011)
This paper presents a fuzzy competitiveness rating (FCR) method for measuring the competitiveness of real estate developers with referring to the Chinese real estate industry. Research data used for analysis were collected from a case study in Green Town Company. Research into the assessment of real estate developers’ competitiveness has been limited. The fuzzy competitiveness rating method is proposed as an alternative effective approach in assessing the competitiveness of real estate developers. The FCR method furnishes real estate developers with innovative solution to assess their competitiveness. By understanding properly organizational competitiveness, real estate developers can adopt appropriate actions and strategies to utilize organization resources more effectively to enhance their competitiveness, thus improve their business performance in the real estate market.First Publish Online: 4 Jul 2011